The development of a basic underhand passing technique teaching model in volleyball for middle school students - Gunawan, Gunawan; Adisjam; Didik Purwanto; Andi Saparia; Humaedi (UNIB Press, 2024)
The fundamental skill of underhand passing in volleyball is essential, but the lack of a teaching model for this skill has resulted in students not fully grasping the basic techniques of volleyball. This research aims to describe the feasibility, practicality, and effectiveness of a teaching model for the basic technique of underhand passing in volleyball for middle school students. The research method used is Research and Development (R&D) with the ADDIE development model. The subjects of this research are middle school students at SMP Al-Azhar Mandiri Palu in grade VIII. The small-scale trial involved 1 teacher and 15 students, while the large-scale trial involved 56 students. The research results indicated that the development of the teaching model for the basic technique of underhand passing in volleyball for middle school students is feasible, with a validity score of 90.03%, categorized as